HUBUNGAN PENGETAHUAN IBU TENTANG PERTUMBUHAN TERHADAP TINGGI DAN BERAT BADAN ANAK USIA 0-5 TAHUN - Anggelina Rahadat; Frenta Helena Simaibang; Dyah Woro Kartiko Kusumo Wardani; Baharika Suci Dwi Aningsih; Lidwina Trieleventa Lumruan Sihombing (Poltekkes Kemenkes Pontianak, 2026)
Background: The growth of children aged 0–5 years, including height and weight, is an important indicator of health status. Mothers' knowledge plays a role in monitoring growth and early detection of disorders. Objective: To analyze the relationship between mothers' knowledge of growth and the height and weight of children aged 0–5 years at the Johar Baru Community Health Center, Central Jakarta. Methods: A cross-sectional correlational design was used with 83 mothers who had children aged 0–5 years selected using accidental sampling. Data analysis was performed using the Chi-square test. Results: Most respondents had high knowledge (92.8%), children with appropriate height (83.1%), and appropriate weight (80.7%). There was a significant relationship between mothers' knowledge and children's height (p = 0.007), while the relationship with children's weight was not significant (p = 0.083). Conclusion: This study shows that high maternal knowledge contributes to appropriate child height, but does not significantly affect weight.